Opportunities in circular agriculture - Balla, Marianna; Szabó, Marianna; Lakatos, Gyula (International Journal of Engineering and Management Sciences, 2019)
Water is the source of life. For the long-term preservation of water resources it is very important to develop sewerage and sewage treatment. Sewage sludge is not primarily a waste that needs to be disposed of but also a secondary raw material or a renewable energy source. Municipal sewage sludge, and sewage sludge composts, contain relatively large quantities of organic matter, so agricultural utilization can be a major potential of its use. The transition to sustainable agriculture is becoming more urgent and increasingly important as it can provide a solution that looks to the future. Sustainable agriculture should work according to natural law, so it should be self-sustaining, that means, cycles, where in to one process the waste created can be used as raw material in the other process. The beneficial effects of sludge on soil include increasing soil organic matter content, increasing soil fertility, nutritional capacity, microbiological activity, and complex fertilizing effects. However, when is applicated, there is always a problem with the occurrence and accumulation of toxic elements and drug residues. The traditional model of economic activity is the linear model. This model ignores the high economic social, and environmental costs of exploiting, transforming and removing of the resources therefore it is not sustainable in the long term. The circular economy offers an alternative model in which the products materials and resources are maintaned as long as possible and the amount of waste is significantly reduced or lost. It is also possible adapt the overtuned ecological, biological balance of agricultural production systems, with a closed loop circular model. According to this model, the development of tillage technologies and the restoration of organic materials and nutrient supply are possible.